Menelaah Fenomena Culture Shock pada Perantau - Leonard Brahmandika (Jurnal Peradaban, 2023)
The focus of this research is to look at the phenomenon of culture shock by migrants. Culture shock is different from cultural lag. In this paper, migrants are students and workers who migrate from their home area to another area. They can migrate temporarily or for a long time. The methodology used is online theme-focus. Through this methodology, the author wants to see various kinds of news in online mass media about students and migrant workers. Their life stories can be a reference for other people who want to migrate. In that life story, there are many life and cultural values ​​that can be applied by other people. This study aims to find the problems that migrants actually experience when they are in other areas. The findings in this research study are the similarities and differences in culture shock experienced by students and migrant workers. Apart from that, there are solutions for these migrants to be able to communicate between cultures when they are in a new area or environment.